How to promote the development of cooperative self-help organization - Buchafwe, Prosper Mkama (KDI School, 2011)
The objective of this study is to explore how credit cooperatives in Tanzania can mobilize financial savings from people's credit funds the so called informal credit market SACCOs, in order to improve agricultural production for national economy growth and poverty alleviation. Cooperatives can play an integral part of a country's development policy. However, experiences in many countries have shown that it is usually a mistake to use credit cooperatives as instruments for the implementation of government policy, rather than allowing them to operate as voluntary self-help organizations of their members. The government should only support by providing access to knowledge, resources and capital, until it is self-sustaining. In Tanzania cooperative did not function as stipulated, this forced the government to intervene, it was discovered that many of the principles were broken. There was widespread misappropriation of funds, nepotism and corruption. This study involved survey conducted in five regions to hear people's opinions on Tanzania cooperative, the result shows positive respond towards SACCOs as tool for poverty reduction.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: PCFs--SACCOs